Ophthalmic Preparations of Interest to Optometrists - Lyle, W M (Canadian Journal of Optometry, 1984)
This paper is essentially a tabulated listing of nearly 200 ophthalmic preparations. It is too lengthy to publish in one issue of the CJO, so it will be presented in parts. The subject is tabulated in the following sections: Tear Supplements and Substitutes, Comfort Solutions. Vasoconstrictors, Decongestants, Astringents and Antihistamines. Topical Antibiotic, or other Antibacterial Preparations. Mydriatics / Cycloplaegics or both. Ophthalmic Ointments.